Molecularly imprinted surface plasmon resonance (SPR) based sensing of bisphenol A for its selective detection in aqueous systems. Issue 11 (7th June 2015) - Shaikh, Huma; Sener, Gulsu; Memon, Najma; Bhanger, Muhammad Iqbal; Nizamani, Shafi Muhammad; Üzek, Recep; Denizli, Adil
<x xml:space="preserve">Abstract</x> Bisphenol A (BPA) imprinted poly(ethylene glycol dimethacrylate-N-methacryloyl-l-phenylalanine-vinyl imidazole) [poly(EGDMA-MAPA-VI)] film deposition on a SPR sensor with improved efficiency is described in this paper.